Sustainable Municipal Solid Waste Management - A case study of Kanpur, India - Mehra, Ashna; Bhargava, Akshey (Journal of New Developments in Chemistry, 2020)
Municipal solid waste generation and disposal is a problem not only in India but all over the world. Presently majority of such waste is being dumped indiscriminately over vacant lands causing problems of odor, methane generation leading to air pollution, leaching effect polluting ground water and runoff polluting water bodies. Technological options are available to treat this solid waste and convert it into usable products but the biggest problem is its segregation preferably at the source of generation or even at the disposal area. Municipal solid waste generated in India consists of 15 percent non biodegradable which has high calorific contents and can be converted into power generation. Remaining 85 percent is degradable which can either be converted into compost or bio fuels. Under the present context, sustainable municipal waste management strategy needs to be evolved and put in place with effective implementation to address the issue of environmental pollution. An attempt has therefore been made by the authors of the present paper to take up a case study of Kanpur, India for managing such wastes having sustainable approach. The authors have worked out trends of population starting from the year 1951 and projected to 2051. Similarly waste generation trends established on the lines of population. An effort has also been made as to how much compost, bio fuel and power can be generated along with economic value to make it sustainable on a time scale.
Keywords: Sustainability; population projections; municipal solid waste; management; solid waste generation; transformation of waste; economic viability